2019
DOI: 10.1155/2019/5960587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deposition Time on the Optoelectronics Properties of PbS Thin Films Obtained by Microwave-Assisted Chemical Bath Deposition

Abstract: PbS thin films with thickness between 100 and 150 nm were grown for the first time by microwave-assisted chemical bath deposition in a commercial automated system with deposition times not exceeding 5 min. X-ray diffraction analysis shows that the thin films have cubic rock salt type structure with good crystallinity. The grain size increased from 18 to 20 nm, as the deposition time increased. Energy dispersive X-ray results confirm that the films are stoichiometric. Optical measurements show that thin films h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The optimal thickness of 399.62 nm was obtained at a deposition time of 5 mins while the least thickness of 294.35 nm was obtained at 1 min of deposition time. This trend of increase in thickness as deposition time increases is similar to those obtained by [26][27][28][29].…”
Section: Thickness Measurementsupporting
confidence: 87%
“…The optimal thickness of 399.62 nm was obtained at a deposition time of 5 mins while the least thickness of 294.35 nm was obtained at 1 min of deposition time. This trend of increase in thickness as deposition time increases is similar to those obtained by [26][27][28][29].…”
Section: Thickness Measurementsupporting
confidence: 87%
“…Even though the formation of flower like structure is characteristic of this preparation technique, the highlighting factor in this study is, the flower like structure have been rarely reported in the case of PbS thin films. There are reports of surface images of PbS thin films with granular structures of well -defined grain boundary [15,16]. The petal-to-petal size of the flowers is found to be slightly increased by increasing the deposition time.…”
Section: Surface Morphologymentioning
confidence: 99%
“…Even though PbS is a widely investigated material due to its varied applications, the field of gas sensors is a less explored area [15][16][17]. The desired characteristic of a thin film as a gas sensor is the roughness of the surface with large surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Many different methods such as electro deposition, chemical bath deposition (CBD), ultrasound deposition, vacuum evaporation, spray pyrolysis, ultrasound deposition, and pulsed laser deposition are used to produce PbS thin films [1], [2].The chemical bath deposition method is an easy, efficient and inexpensive method that is widely used to produce thin-film with many different materials [3]. The CBD method can be used for the production of PbS thin films with highquality since parameters such as stirring speed, deposition temperature, deposition time and solution pH can be easily controlled [4].…”
Section: Introductionmentioning
confidence: 99%